The Relationship between Dynamic Balance Ability and Low Limb Isokinetic Muscle Function of Elite Judo Athletes - Jong Baek Lee; Young Kyun Kim (Asian Society of Kinesiology, 2020)
OBJECTIVES The purpose of this study is to examine the relationship between lower extremity isokinetic muscle strength and dynamic balance ability of elite judo athletes and improve the efficient dynamic balance ability of athletes. METHODS A total of 26 male and female judo national candidates (13 males and 13 females) were participated. Isokinetic strength and dynamic balance in three consecutive areas of the lower limbs (knee, hip, waist) were measured. Multiple regression analysis step selection method was used to analyze the correlation between isokinetic strength measurement variables and dynamic balance ability. In addition, the results were analyzed by dividing the difference of fitness variables between male and female athletes and male and female athlete groups. RESULTS The male athlete group showed higher muscle strength in all areas of isokinetic strength (p <.01). Stability was statistically significantly higher (p <.05). There was interrelationship between the lower extremity isokinetic strength and the dynamic balance of the lower extremities in male and female athletes. The trunk flexion showed the highest correlation with the dynamic balance in the male athletes, and trunk flexion and hip extension in female athletes. CONCLUSIONS The trunk muscle strength showed the highest correlation with the dynamic balance ability in male and female athletes.